Dynamic scheduling method of service function chain executors based on the mimic defense architecture - Chuanhuang LI; Jingjing TANG; Yangting CHEN; Rui LEI; Chao CHEN; Weiming WANG (Dianxin kexue, 2022)
Faced with the problem that static and lagging traditional defense technologies cannot effectively deal with new network attacks, according to the theory of mimetic security defense, a defense architecture of mimic service function chain (MSFC) based on the data forwarding level was proposed, and an execution dynamic scheduling method based on the decision feedback was further proposed.The method took the abnormal executor information fed back by the decision maker, the heterogeneity of executors and the actual load of the system as the scheduling influencing factors, so that the scheduling method can be adjusted adaptively according to the actual changes of the network.In addition, the scheduling method used decision feedback to adjust the scheduling time, so as to achieve the best balance between system cost and security, and reduce the resource overhead of the system.Simulation results showed that the scheduling method can select a set of highly heterogeneous actuators that better meet the current network requirements on the basis of balancing the system cost and security, so as to improve the security and reliability of the system.